The Role of Intestinal Microbiota in Celiac Disease and Further Therapeutic Perspectives - Belei, Oana; Jugănaru, Iulius; Basaca, Diana-Georgiana; Munteanu, Andrei Ioan; Mărginean, Otilia (Life (Basel, Switzerland), 2023)
Celiac disease (CD) is an immune-mediated enteropathy caused by exposure to gluten and related prolamins in genetically susceptible individuals. It is a complex genetic disorder with multiple contributing genes. Linkage studies have identified several genomic regions that probably contain CD susceptibility genes. The most important genetic factors are HLA-DQ2 and DQ8. Several known environmental triggers promote the onset of CD at any age after gluten introduction in individuals with a genetic background, such as viral infections and intestinal dysbiosis. Recent publications have described the interference of the intestinal microbiome in gluten metabolism, modulation of local immune reactions, and in maintaining normal gut permeability. These results have promoted further lines of research on the benefit of probiotic administration to prevent disease onset or alleviate clinical symptoms along with a gluten-free diet (GFD). The relationship between gut microbiome changes and the onset of CD is incompletely understood, still being the subject of current research. This narrative review analyzes the interplay between environmental factors, intestinal microbiome alterations, and the course of CD. Furthermore, this review sets out to discuss if modulation of intestinal microflora with pre- and probiotics along with a GFD could represent a reliable therapeutic target for celiac patients.